2021
DOI: 10.1002/lno.11963
|View full text |Cite
|
Sign up to set email alerts
|

Stratification strength and light climate explain variation in chlorophyll a at the continental scale in a European multilake survey in a heatwave summer

Abstract: Author Contribution Statement: D.D. analyzed and worked on data visualization, coordinated feedback from coauthors, and wrote the manuscript. E.M. coordinated the EMLS, collected data, curated the dataset, analyzed the data, and contributed to writing the manuscript. B.I. conceived the idea for the EMLS, contributed to discussions throughout the study and to the writing of the manuscript. D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 88 publications
(115 reference statements)
1
2
0
Order By: Relevance
“…The average satellite observation frequency for the dataset over the study period was 1.7 days, which is close to the recommended sampling frequency of once every two days required to detect short-term perturbations in phytoplankton dynamics [43] and compares favorably with large-scale in situ synoptic sampling efforts. It is also well above the frequencies recommended by EU policy [44][45][46]. The timing of Chl-a and turbidity peaks after a fire occurrence were also identified by this analysis.…”
Section: Data and Statistical Analysissupporting
confidence: 60%
“…The average satellite observation frequency for the dataset over the study period was 1.7 days, which is close to the recommended sampling frequency of once every two days required to detect short-term perturbations in phytoplankton dynamics [43] and compares favorably with large-scale in situ synoptic sampling efforts. It is also well above the frequencies recommended by EU policy [44][45][46]. The timing of Chl-a and turbidity peaks after a fire occurrence were also identified by this analysis.…”
Section: Data and Statistical Analysissupporting
confidence: 60%
“…However, the differences were not significant. It has been shown that under high nitrogen and phosphorus loading, heatwaves favor algal growth more than continuous warming, potentially due to the fact that extreme temperature fluctuations facilitate growth of cyanobacteria at high levels of nutrients. , As shown by Chen et al and Donis et al., summer extreme climate events (i.e., heatwaves) facilitate an increased productivity and an increased cycling of nutrients in the pelagic, resulting in a higher peak of cyanobacteria biomass in lake ecosystems. Meanwhile, heatwaves may, directly or indirectly, favor cyanobacteria by increasing the stability of the water column, which can provide optimal buoyancy conditions, or by facilitating sediment nutrient release .…”
Section: Resultsmentioning
confidence: 99%
“…However, a shift in the wind pattern was observed before the end of May, indicating the end of the Northeast Monsoon, and marking the start of the Southwest Monsoon. Along with wind speed, the wind direction can be an indicator of a high concentration of different water quality parameters in the surface of the lake and can also act as a regulator of the physical environment since it can either disrupt or deepen the layer of stratification, depending on the morphology of the water body [53,54].…”
Section: Thermal Structure Of the Lakementioning
confidence: 99%